PENGEMBANGAN PROGRAM PEMASARAN PENDIDIKAN - Roichatul Mabruroh; Millatul Fadhilah (PROPHETIK Jurnal Kajian Keislaman, 2024)
Today the world has entered the globalization so the impact on climate change that is competitive on all fronts. Globalization is a form of this power triggers changes in all segments of life. So what happens is that increased competition is high in all areas, including in education. This dynamic climate, it is difficult for the organization to survive well include menggembangkan themselves and meet the rapidly changing demands of customers. This condition also applies to all organizations that are profit or non-profit. This also applies to education, even though education is not included in the profit agency, but its management can not be done traditionally but require special ability that educational output has high competitiveness to compete in the global market. These go a paradigm shift in looking at education at first level only seen in the social aspect but more than that more education on corporete. This means that educational institutions be understood as the production of educational services that its output will be purchased by consumers. Then the educational institutions should be able to market their products in order to buy the market, of course, that in the interest of the market, the quality should be able to meet and satisfy the consumer market, so that products sold on the market.